Konsep Miranda Rule dalam Hukum Pidana di Indonesia Perspektif Maqasid al-Shari’ah - Handoko, Priyo; Farida, Anis (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2021)
This article examines the application of the Miranda rule concept in Criminal Procedure Law in Indonesia which is viewed from the perspective of maqa>sid ash-syari>'ah. The research method used in this research is normative law which is described in an explorative-qualitative manner. The results of the study explain that the existence of The Miranda Rule concept in the Criminal Procedure Code in Indonesia is not entirely included. It is limited only to Article 52 of the Criminal Code which gives freedom to suspects or defendants in giving information. The right to remain silent is not justified in the Criminal Procedure Code as in Mirnada Right. This is because in some cases there was coercion by the authorities which then led to an inaccurate decision by the court. So maqa>sid ash-syari>'ah views the concept of the miranda rule of benefit to be applied in criminal law in Indonesia, especially the Criminal Procedure Code as a form of safeguarding human dignity and human rights. Mistakes or harm should be minimized or even eliminated when dealing with human life or human dignity. So the author concludes that it is necessary for lawmakers or in this case the legislature and the government to carry out legal reforms to the existence of the rights of suspects or defendants in procedural law in accordance with the objectives or benefits of a law.